2013
DOI: 10.1002/ajmg.a.35972
|View full text |Cite
|
Sign up to set email alerts
|

Views and preferences for the implementation of non‐invasive prenatal diagnosis for single gene disorders from health professionals in the united kingdom

Abstract: Non-invasive prenatal diagnosis (NIPD) will offer new options in prenatal diagnosis for carriers of single gene disorders. This will affect carrier couples and health professionals involved in prenatal care. The aim of this study was to determine health professional opinions on NIPD for single gene disorders to guide development of infrastructure required for implementation. A qualitative approach was adopted using focus groups (N = 17) and one-to-one interviews (N = 30) with health professionals from a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 30 publications
7
72
0
Order By: Relevance
“…14,15 While service users cite the earlier timing of the test and safety for the fetus 16 as major advantages of NIPD, health professionals were positive, but expressed reservations such as concerns about informed consent and potential 'routinisation' of a test that can be done on a 'simple' blood test. 17 It is clear, therefore, that before the full implementation of NIPD into clinical practice, ethical and social issues should be explored. 18 Specific ethical issues around NIPD were outlined in a paper by Deans et al, 19 who used examples to illustrate how the ethical principles of autonomy, privacy and fairness could be at risk with the use of NIPD.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 While service users cite the earlier timing of the test and safety for the fetus 16 as major advantages of NIPD, health professionals were positive, but expressed reservations such as concerns about informed consent and potential 'routinisation' of a test that can be done on a 'simple' blood test. 17 It is clear, therefore, that before the full implementation of NIPD into clinical practice, ethical and social issues should be explored. 18 Specific ethical issues around NIPD were outlined in a paper by Deans et al, 19 who used examples to illustrate how the ethical principles of autonomy, privacy and fairness could be at risk with the use of NIPD.…”
Section: Introductionmentioning
confidence: 99%
“…First, there are concerns stemming from the potential routine use of NIPT in prenatal care and the threats this routinization may pose to reproductive autonomy. In the absence of risk to the pregnancy, clinicians may see counseling and informed consent as less important than for invasive testing [van den Heuvel et al, 2010;Deans and Newson, 2011;Hill et al, 2013], as is currently the case regarding non-invasive screening tests [Seavilleklein, 2009;Kellogg et al, 2014]. Routinization may also increase pressure on women to test, thus limiting -rather than promoting -their liberty to choose [Lewis, Silcock and Chitty, 2013].…”
mentioning
confidence: 99%
“…In the early papers that discussed it as a diagnostic test, it was suggested that access to genetic information in the first trimester would allow women and their families more time to make a decision regarding their pregnancy management: to prepare for the birth of a child with special needs or to make a decision regarding termination of pregnancy [33]. For those who decided to terminate, NIPT would allow an earlier termination, making it medically safer and allowing it to occur when maternal-fetal attachment might be less established and when the pregnancy was not yet socially visible [27,34].…”
Section: Findings 1 Nipt and Reproductive Autonomymentioning
confidence: 99%
“…argued that NIPT significantly modified the decision-making context and might increase the pressure on women by leaving them with "no reasonable argument" for rejecting the test [27,33,34,36,39].…”
Section: The Routinization Of Nipt: Impact On Decision-making and Infmentioning
confidence: 99%